Impact of Fringing Field on Shell Radius and Spacer Dielectric on Device Performance of InAs-GaSb Core-Shell Nanowire nTFET. (7th June 2021) - Joseph, H. Bijo; Singh, Sankalp Kumar; Nagarajan, Venkatesan; Anandan, Deepak; Chang, Edward Yi; Kakkerla, Ramesh Kumar; D, John Thiruvadigal
Abstract : A comprehensive investigation with the help of 3D device simulation, we demonstrate the impact of fringing field on shell radius of InAs-GaSb core–shell nanowire n-channel tunnel field effect transistor (TFET) in this paper. Increase in shell radius intensifies the magnitude of fringing electric field towards shell region. This results in generation of depletion zone in the shell near the gate edge affects the device performance metrics such as on current and threshold voltage. It is demonstrated that by appropriate gate engineering the influence of fringing electric field can be circumvent. High-k spacer dielectric at the gate underlap shows improvement in device performance metrics such as on current with sub 2.3 k B T q subthreshold swing. An investigation of the effect of drain voltage on the device characteristics exhibits the privation of tunneling resistance limited region. Furthermore, the output characteristics for such an architecture bear a resemblance to long channel MOSFET (metal oxide semiconductor field effect transistor).